Migratory Consequences of the Covid-19 Pandemic in Armenia - Vartikyan, Aram; Demirchyan, Movses (Journal of Sociology: Bulletin of Yerevan University, 2022)
The socio-economic, political, and even cultural consequences of the Covid-19 pandemic are more than obvious. They affect the whole world and are relevant in all spheres and levels of social and public life. Numerous anti-pandemic measures, mainly the closure of borders, restrictions on the movement of citizens, and isolation hit the businesses and economies of different volumes and intensities. The spheres of tourism and services are special here and the ones where the organization of activities is based on the circulation of people and face-to-face interactions. The effective functioning of a number of social institutions was disrupted. Negative consequences were also relevant in the case of various migration flows. Having been actively involved in the migration for many years, the Armenian society is not immune to the effects of Covid-19. Based on the available literature, articles, reports, various publications and rich statistical data, the article presents in detail the impact of the pandemic on Armenian migration processes. The paper introduces the migration context of Armenia, the effects of the pandemic on the activities of a number of migrants and related groups. Conflicts of adapting to and overcoming the crisis, formal and informal tactics, approaches and practices are analyzed.
Keywords: Covid-19 Pandemic; Migration; Labor migrants; Migrants families; Masculinity; Refugees; Vulnerability; Violence; Discrimination